Hfe Gene Knock-Out in a Mouse Model of Hereditary Hemochromatosis Affects Bodily Iron Isotope Compositions - Albalat, Emmanuelle; Cavey, Thibault; Leroyer, Patricia; Ropert, Martine; Balter, Vincent; Loréal, Olivier (Frontiers in Medicine, 2021)
Hereditary hemochromatosis is a genetic iron overload disease related to a mutation within the Hfe gene that controls the expression of hepcidin, the master regulator of systemic iron metabolism. The natural stable iron isotope composition in whole blood of control subjects is different from that of hemochromatosis patients and is sensitive to the amount of total iron removed by the phlebotomy treatment. The use of stable isotopes to unravel the pathological mechanisms of iron overload diseases is promising but hampered by the lack of data in organs involved in the iron metabolism. Here, we use Hfe-/- mice, a model of hereditary hemochromatosis, to study the impact of the knock-out on iron isotope compositions of erythrocytes, spleen and liver. Iron concentration increases in liver and red blood cells of Hfe-/- mice compared to controls. The iron stable isotope composition also increases in liver and erythrocytes, consistent with a preferential accumulation of iron heavy isotopes in Hfe-/- mice. In contrast, no difference in the iron concentration nor isotope composition is observed in spleen of Hfe-/- and control mice. Our results in mice suggest that the observed increase of whole blood isotope composition in hemochromatosis human patients does not originate from, but is aggravated by, bloodletting. The subsequent rapid increase of whole blood iron isotope composition of treated hemochromatosis patients is rather due to the release of hepatic heavy isotope-enriched iron than augmented iron dietary absorption. Further research is required to uncover the iron light isotope component that needs to balance the accumulation of hepatic iron heavy isotope, and to better understand the iron isotope fractionation associated to metabolism dysregulation during hereditary hemochromatosis.